The learning management system discussion board as change agent - Dobozy, Eva (Inderscience Publishers, 2015)
Taking the concept of ‘Learning Design’ as a starting point, this paper explores design decision for the construction of a joint Blackboard site with embedded discussion board for students studying the same unit in either on-campus or online mode. In particular, the discussion board was designed to function as a communal space and central meeting point, inviting the disparate groups to ‘mingle’ and engage in border crossing behaviours and informal ethics training. The discussion board design was approached from a ‘built pedagogy’ perspective in conjunction with Learning Design principles and was underpinned by a Bourdieuian dispositional theory of action standpoint. This paper will provide an argument for the need to break down artificial barriers between learners and will illustrate how discussion boards can be employed to function as change agents.